Education of making and distribution of betel leaves hand sanitizers to kefamenanu Pasar Baru sellers - Mada, Grandianus Seda; Tea, Marselina Theresia Djue; Pardosi, Lukas; Welsiliana; Pramita, Dira Asri; Batu, Matius Stefanus; Siahaan, Desta Gloria (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The business’ level, lack of knowledge about the making process and use of hand sanitizers from natural ingredients caused sellers in Pasar Baru Kefamenanu do not apply the health protocols during transactions with buyers. Therefore, there needs to be educated about natural ingredients that can be used as hand sanitizers, the making process, and how to use them. Natural ingredients that are found in Kefamenanu are betel leaves. Education on making hand sanitizers from betel leaves helps sellers to be able to make their own hand sanitizers. The addition of aloe vera to betel leaves extract aims to make the liquid hand sanitizer becomes softer. While lime and perfume are to get rid of the betel leaves’ smell. The distribution of hand sanitizers that has been made can be an example of products from natural ingredients and the storage bottles provided can be used as a refill place for hand sanitizer.